Typhoid Fever – Will we able to control this in Pakistan? - Saleem, Ali Faisal (Infectious Diseases Journal of Pakistan, 2022)
Salmonella typhi and Salmonella paratyphi causes typhoid fever and this is endemic in Pakistan. Every year there is consistency in cases reported across Pakistan. More than 20,000 cases were reported during 2017-2019 period. Disease is associated with increasing morbidity and mortality. It is transmitted through oral-fecal route. Hand hygiene, water sanitation and good control on sewage practices can prevent its transmission from person to person. The disease fever lasts a little long compared to other pathogenic bacterial illnesses and mainly affects gastrointestinal and hepatic system of the body affecting appetite and linear growth of the affected person even post-cure. Cephalosporins were the treatment of choice in the past, however in last two years there is an increasing resistance reported across Pakistan. A new classification of non-resistant typhoid fever, multi-drug resistant (MDR) typhoid fever and extensive drug resistant (XDR) typhoid fever was established in 2018. XDR typhoid fever is sensitive against azithromycin and carbapenems; and currently are drug of choice in MDR typhoid. The presence of XDR Salmonella typhi in Pakistan is mainly due to poor WASH (water, sanitation and hygiene) practices across the country. Despite the endemicity there wasn’t any approved official typhoid vaccination in EPI Pakistan till 2018.